Penerapan metode pembelajaran Gallery Walk untuk meningkatkan kerja sama pada pembelajaran pancasila kelas V - Amanda Destyana Putri; Wahyu Kurniawati; Henry Aditia Rigianti (Borobudur Educational Review, 2024)
The aim of this research is to examine the use of the gallery walk method to increase student cooperation in the Pancasila learning process. The Gallery Walk method is an approach that encourages students' active participation in various learning activities that involve moving between learning points in the classroom. The research method used is classroom action research carried out over two cycles. The setting of this research is in class V of Kasongan State Elementary School with research subjects totaling 23 students. Data was collected through observation, interviews and documentation. The data analysis technique is carried out descriptively by describing each action that has been carried out. The research results show that there is an increase in student cooperation after implementing the gallery walk method in the learning process. Keywords: gallery walk method. Student cooperation, Pancasila